Integrasi Budaya dalam Pembelajaran Kimia Hijau: Pengaruh E-Modul Berbasis Culturally Responsive Teaching terhadap HOTS - Hidayati, Ririn Eva (Balai Diklat Keagamaan Surabaya, 2025)
This study focuses on developing a green chemistry e-module based on Culturally Responsive Teaching (CRT), designed to improve high-order thinking skills (HOTS) of class X students of MAN 1 Malang City. The development of the e-module follows the 4D model (Define, Design, Develop, Disseminate), involving expert validation and trials on students. The research instruments include HOTS tests, observations, interviews, questionnaires, and documentation. The validation results show that this e-module is classified as